2021
DOI: 10.5565/rev/analisi.3411
|View full text |Cite
|
Sign up to set email alerts
|

Més enllà de reptes i balls virals: TikTok com a vehicle per al discurs desinformatiu i la verificació d’informació a Espanya, Portugal, el Brasil i els Estats Units

Abstract: This paper analyses the narrative of disinformation disseminated through the social network TikTok, a network which is popular at a global level and whose users are mainly young or very young. To do so, a study was carried out on the content of publications on TikTok in four countries with different idiosyncrasies and national realities: Spain, Portugal, Brazil, and the United States. Interviews were also conducted with fact-checking agencies on the potential for misinformation and fact-checking potential on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The central objective is to analyze the corporate policies that TikTok has implemented (mainly at the European level), the issues they aim to deal with, and how the social network has monitored and complied with said policies from 2020 to 2024, given that TikTok "is becoming a new home for fake news stories, manipulated media, and other types of misinformation" (Newman, 2022a(Newman, , 2022b. Unlike previous research that has focused primarily on analyzing the activity of verification agencies and fact-checkers (Ufarte Ruíz and Murcia Verdú, 2018;Alonso-López et al, 2021;Sidorenko-Bautista et al, 2021;Dafonte-Gómez et al, 2022;García-Marín and Salvat-Martinrey, 2022;Arrieta-Castillo and Rubio Jordán, 2023;Hidalgo Cobo and Puebla-Martínez, 2023) this study focuses on the platform's own corporate strategy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The central objective is to analyze the corporate policies that TikTok has implemented (mainly at the European level), the issues they aim to deal with, and how the social network has monitored and complied with said policies from 2020 to 2024, given that TikTok "is becoming a new home for fake news stories, manipulated media, and other types of misinformation" (Newman, 2022a(Newman, , 2022b. Unlike previous research that has focused primarily on analyzing the activity of verification agencies and fact-checkers (Ufarte Ruíz and Murcia Verdú, 2018;Alonso-López et al, 2021;Sidorenko-Bautista et al, 2021;Dafonte-Gómez et al, 2022;García-Marín and Salvat-Martinrey, 2022;Arrieta-Castillo and Rubio Jordán, 2023;Hidalgo Cobo and Puebla-Martínez, 2023) this study focuses on the platform's own corporate strategy.…”
Section: Methodsmentioning
confidence: 99%
“…Yes, TikTok aims to control the existing information flows on the platform. Nevertheless, there is a significant flow of content that encourages disinformation: sometimes this occurs unintentionally, though oftentimes it does so intentionally (Alonso-López et al, 2021).…”
Section: Content Consumption By the Platform's Younger Usersmentioning
confidence: 99%
“…Reasoning and critical skills are essential skills, especially for teenagers facing daily misinformation on platforms like social media [49]. A Twitter study showed that false news is more frequently shared than true news [50], and platforms like TikTok often promote disinformation [52]. It's vital to provide youth with tools to discern and counteract hoaxes [53].…”
Section: Student's Personal Epistemology and Critical Thinkingmentioning
confidence: 99%
“…An additional study, also looking at the 2016 United States election, found that engagements with false or misleading content reached a peak of roughly 160 million per month at the end of 2016. By contrast, the top 38 major news sites, including the New York Times, Wall Street Journal, CNN, Fox News, average around 200-250 million Facebook engagements per month (Allcott, Gentzkow and Yu, 2019 [32]).…”
Section: Engagement With False and Misleading Digital Contentmentioning
confidence: 99%